Circadian rhythm of juveniles of brown-marbled grouper and orange-spotted grouper - Mukai, Yukinori (2013)

(untitled)
There are several methods to give feed to fish, for example manual feeding, automatic feeding (using timer feeder) and demand feeding (self feeding). Recently automatic feeding and demand feeding are expected as new feeding methods for aquaculture. Because these feeding methods have advantages, such as, the staffs of fish farms do not need feeding at night time, if fish farms use these new methods. However, there are no data about fish circadian rhythms about both of brown-marbled grouper Epinephelus fuscoguttatus and orange-spotted grouper, Epinephelus coioides. Therefore this study was conducted to obtain the basic data about feeding activity during 24 hours for new feeding methods. The recording of circadian rhythms was done in the hatchery of INOCEM, IIUM Kuantan Campus. During the experiment under natural photoperiod, 15 juveniles were placed in 200 L gray rectangular fibreglass tank [0.8 m (L) x 0.4 m (W) x 0.7 m (H)]. Swimming activities of juveniles during night time were recorded by a colour CCD camera (WAT-232/NTSC, DC 12V) connected to a television and a DVD recorder under an infrared ray LED 850 nm (WTW, SM-104-850). The activities during daytime were recorded by a Sony handycam camcorder (Sony HDR-SR10). The swimming activities of the juveniles were recorded for 24 hours. The juveniles of brown-marbled grouper and orange-spotted grouper were obtained from private fish farms. Both of grouper species show higher activities in the daytime than the night time. These grouper species seems to be typical diurnal species. These data are useful basic information to develop the feeding devises. For example, we can use these data for setting up the automatic feeding devises.